Gestational Age and Maternal Serum 25-hydroxyvitamin D Concentration Interact to Affect the 24, 25-dihydroxyvitamin D Concentration in Pregnant Adolescents. Issue 6 (23rd May 2018) - Best, Cora M; Pressman, Eva K; Queenan, Ruth Anne; Cooper, Elizabeth; Vermeylen, Françoise; O'Brien, Kimberly O
Abstract: Background: Interpretation of serum vitamin D biomarkers across pregnancy is complex due to limited understanding of pregnancy adaptations in vitamin D metabolism. During pregnancy, both gestational age and serum 25-hydroxyvitamin D [25(OH)D] concentrations may influence the concentrations of 1, 25-dihydroxyvitamin D [1, 25(OH)2 D], 24, 25-dihydroxyvitamin D [24, 25(OH)2 D], and parathyroid hormone (PTH). Objective: We aimed to identify predictors of change in serum 25(OH)D across gestation in pregnant adolescents and to assess the contribution made by cholecalciferol (vitamin D3 ) supplementation. We sought to determine whether gestational age and 25(OH)D concentration interacted to affect serum 1, 25(OH)2 D, 24, 25(OH)2 D, or PTH. Methods: Pregnant adolescents ( n  = 78, 59% African American, mean ± SD age: 17 ± 1 y) living in Rochester, NY (latitude 43°N) were supplemented with 200 IU or 2000 IU vitamin D3 /d and allowed to continue their daily prenatal supplement that contained 400 IU vitamin D3 . Serum was collected at study entry (18 ± 5 wk of gestation), halfway through study participation, and at delivery (40 ± 2 wk). Serum concentrations of the biochemical markers were modeled with linear mixed-effects regression models. Results: Vitamin D3 supplement intake and season of delivery determined change in 25(OH)D across pregnancy. Fall-winter delivery was associated with a decline in 25(OH)D unless vitamin D3 supplement intake was >872 IU/d. The interaction of gestational age and 25(OH)D affected 24, 25(OH)2 D concentrations. For a given 25(OH)D concentration, model-predicted serum 24, 25(OH)2 D increased across gestation except when 25(OH)D was <13 ng/mL. Below this threshold, 24, 25(OH)2 D was predicted to decline over time. Mean serum 1, 25(OH)2 D was elevated (>100 pg/mL) throughout the study. Conclusion: Our results suggest that when maternal serum 25(OH)D was low, its catabolism into 24, 25(OH)2 D decreased or remained stable as pregnancy progressed in order to maintain persistently elevated serum 1, 25(OH)2 D. Furthermore, in adolescents living at latitude 43°N, standard prenatal supplementation did not prevent a seasonal decline in 25(OH)D during pregnancy. This study was registered at clinicaltrials.gov as NCT01815047.